Promoting wellbeing and empowerment via Youth First: Exploring psychosocial outcomes of a school-based resilience intervention in Bihar, India - Leventhal, Katherine S.; Cooper, Peter L.; DeMaria, Lisa M.; Priyam, Priyadarshi; Shanker, Hari; Andrew, Gracy; Leventhal, Steve (Frontiers in Psychiatry, 2022)
Youth worldwide are struggling with increased mental health concerns. As youth in low- and middle-income countries make up more than 20% of the world’s population, finding ways to improve their psychosocial wellbeing is crucial. CorStone’s Youth First program is a school-based psychosocial resilience program that seeks to improve the mental, physical, social, and educational wellbeing of early adolescents. The program is delivered via trained government schoolteachers who facilitate students’ learning and development in small groups using a discussion and activity-based curriculum. In August 2021, a study among 322 adolescents was conducted to investigate and compare program participants’ and non-participants’ understanding and use of inter- and intra-personal psychosocial skills. Focus group discussions were held with students in eight intervention schools and four comparable schools not receiving the intervention (control). Through the focus group discussions, students provided their opinions, thoughts, and ideas about vignettes describing challenges that youth in their communities frequently face, including early marriage and financial pressures. Analysis integrated qualitative and quantitative approaches, consisting of an iterative thematic analysis process followed by quantizing data and conducting t-tests. Youth who had received Youth First had greater awareness of problems, perspective-taking, problem-solving strategies, helping approaches, awareness of their own strengths, and visions for the future, when compared with the control group. Findings provide insights into potential outcomes for measurement in future evaluations of mental health promotion and prevention programs among youth in LMICs.